Preparation method and application of magnesium-air battery anode material Mg-Sr-Ge ternary alloy
By using Mg-Sr-Ge ternary alloy as anode material in magnesium air batteries, the problem of low anode efficiency and slow cathode oxygen reduction reaction kinetics is solved, and a higher discharge voltage and specific energy is achieved, extending the service life of the battery.
Patent Information
- Application Number
- CN202411835992.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
Existing magnesium air batteries face the problems of low anode efficiency and slow kinetics of cathode oxygen reduction reactions, which lead to self-discharge and discharge losses and reduce the service life of the battery.
The Mg-Sr-Ge ternary alloy is used as the anode material for the magnesium air battery. By adding strontium (Sr) and germanium (Ge) elements, the discharge voltage of the magnesium anode is increased, the self-corrosion of hydrogen evolution is suppressed, the grain size of magnesium is refined, and the microstructure is optimized, thereby improving the anode utilization efficiency.
It significantly improves the anode utilization efficiency and specific energy of magnesium air batteries, extends the service life of the battery, and reduces the preparation cost.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium-air battery electrode materials, and in particular, relates to a preparation method and application of a magnesium-air battery anode material Mg-Sr-Ge alloy. Background Art
[0002] In the context of the growing demand for energy supply, magnesium-air batteries, as a new type of energy storage and conversion device, have attracted widespread attention due to their safety, pollution-free and high specific energy density. Magnesium alloys, as the lightest metal structural material, have the advantages of being non-toxic, pollution-free, abundant in reserves and low in price. They have a low standard electrode potential (-2.37 Vvs. SHE) and a high theoretical specific capacity (2200 mAh g -1 ), high energy density (6800 mWh g -1 ) and low density (1.74 gcm -3 ), is considered to be an ideal anode material for air batteries. Magnesium-air batteries, with their unique semi-open structure, save internal battery space and reduce the weight of the battery itself, and have been used in electric vehicles, special military equipment and other fields.
[0003] However, magnesium-air batteries still face some challenges, mainly low anode efficiency and slow cathode oxygen reduction reaction kinetics. Magnesium is easily polarized to a level higher than its self-corrosion potential during discharge, resulting in self-discharge and discharge loss, which reduces the anode efficiency and the battery life. Although a lot of research has been devoted to solving these problems, choosing the right magnesium-air battery anode material is still the key.
[0004] In recent years, magnesium battery technology has made continuous breakthroughs and is expected to achieve commercial application, especially in deep-sea high-pressure environments, where significant progress has been made. In addition, the energy density of magnesium-air batteries is already higher than that of lithium iron phosphate batteries, showing its potential in the field of energy storage. Therefore, the development of new and efficient magnesium-air battery anode materials is of great significance to promote the development and application of magnesium-air battery technology.
[0005] Based on this, this application was developed. Summary of the invention
[0006] The present invention aims to solve the limitations of existing magnesium-air batteries and proposes a new type of magnesium-air battery anode material - Mg-Sr-Ge ternary alloy. The standard electrode potential of Sr (strontium) is more negative than that of Mg (magnesium) (-2.90 V vs. SHE), which helps to increase the discharge voltage of the magnesium anode. At the same time, the addition of Ge (germanium) can increase the hydrogen evolution overpotential of magnesium alloys and effectively inhibit the self-corrosion phenomenon of hydrogen evolution. In addition, the addition of Sr and Ge can also refine the grain size of magnesium and optimize the microstructure of the magnesium anode. These improvements work together to improve the anode utilization efficiency of magnesium-air batteries, thereby enhancing battery performance.
[0007] The present invention also provides a method for preparing the above-mentioned magnesium-air battery anode material Mg-Sr-Ge ternary alloy and its application in magnesium-air batteries.
[0008] To achieve the above object, the present invention adopts the following technical solution: A magnesium-air battery anode material Mg-Sr-Ge ternary alloy, the chemical composition of which is calculated by mass percentage: strontium (Sr) 0.1-2.0 wt%, germanium (Ge) 0.1-2.0 wt%, and the balance is magnesium (Mg). The alloy is prepared using pure magnesium ingots, high-purity germanium and Mg-Sr alloy as main raw materials, and may contain trace amounts of unavoidable impurities.
[0009] As a preference, the above-mentioned magnesium-air battery anode material Mg-Sr-Ge ternary alloy has the following chemical compositions by mass percentage: 0.1 wt % strontium, 0.1 wt % germanium, and the balance magnesium.
[0010] As a preference, the above-mentioned magnesium-air battery anode material Mg-Sr-Ge ternary alloy has the following chemical compositions by mass percentage: 0.1 wt % strontium, 0.5 wt % germanium, and the balance magnesium.
[0011] The present invention provides a method for preparing the above-mentioned magnesium-air battery anode material Mg-Sr-Ge ternary alloy, which comprises the following steps: (1) Accurately weigh the raw materials, including pure magnesium ingot, pure germanium and Mg-Sr master alloy, in proportion, and carefully remove the surface oxide layer to ensure the purity and reactivity of the materials during the smelting process; (2) Put the processed raw materials together into a graphite crucible of a vacuum melting furnace, then evacuate and introduce protective gas to prevent oxidation; in the protective atmosphere, heat the vacuum melting furnace until the raw materials are completely melted, stir, and then keep the temperature for 5-20 minutes to stabilize the internal structure of the alloy, and finally cast the molten alloy and cool it to room temperature with the furnace to obtain a cast ternary alloy. The cast alloy can be directly used as anode material for magnesium-air batteries without further processing.
[0012] Specifically, in step (2), the heating temperature may be 720° C.-750° C., and a stirring head may be used for stirring for 10-30 minutes.
[0013] Furthermore, the protective atmosphere used may be high-purity argon gas with a purity not less than 99.99%. The Mg-Sr master alloy used may preferably be a Mg-20Sr master alloy.
[0014] The present invention provides the use of the above Mg-Sr-Ge ternary alloy as an anode material for magnesium-air batteries. Compared with the traditional commercial AZ31 anode material, it exhibits higher discharge voltage, specific capacity and specific energy, and has better battery performance.
[0015] The present invention also provides a magnesium-air battery, the core components of which include an electrolyte, an air cathode and the above-mentioned anode material Mg-Sr-Ge ternary alloy. Furthermore, in this battery design, the electrolyte can be a 3-4 wt.% (preferably 3.5 wt.%) sodium chloride (NaCl) solution. The air cathode can be a common product on the market, or prepared using conventional technology in the field. This air cathode is mainly composed of a gas diffusion layer, a current collecting layer and a catalyst layer, wherein the catalyst layer contains a manganese dioxide catalyst, Compared with the prior art, the present invention has the following beneficial effects: 1) The standard electrode potential of the Sr (strontium) element added in the present invention is more negative than that of Mg (magnesium) (-2.90 V vs. SHE), and this property helps to increase the discharge voltage of the magnesium anode. At the same time, the addition of Ge (germanium) can increase the hydrogen evolution overpotential of the magnesium alloy and effectively inhibit the self-corrosion phenomenon of hydrogen evolution. In addition, the addition of Sr and Ge can also refine the grain size of magnesium and optimize the microstructure of the magnesium anode. These improvements work together to improve the anode utilization efficiency of magnesium-air batteries, thereby enhancing battery performance. Through these innovative alloy designs, the present invention aims to bring significant performance improvements to the field of magnesium-air batteries.
[0016] 2) The Mg-Sr-Ge ternary alloy preparation process adopted in the present invention is carried out by a vacuum induction melting furnace, which not only simplifies the operation process but also effectively prevents the mixing of new impurities. This method is not only easy to implement but also ensures the purity and quality of the alloy.
[0017] 3) The Mg-Sr-Ge ternary alloy anode material of the present invention exhibits higher discharge voltage, specific capacity and specific energy than the AZ31 alloy anode material on the market. This new alloy anode material not only has a low preparation cost, but also a simple smelting process, and can significantly improve the discharge performance of magnesium-air batteries. Therefore, the Mg-Sr-Ge ternary alloy anode material has broad application prospects and is expected to become an important material to promote the development of magnesium-air battery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The discharge performance diagrams of the magnesium-air battery anode material Mg-Sr-Ge ternary alloy and the commercial AZ31 alloy prepared in Examples 1 and 2 of the present invention are as follows: (a) average discharge voltage; (b) anode utilization efficiency; (c) specific capacity; (d) specific energy; Figure 2 Figures a to f are surface and cross-sectional characterization images of the magnesium-air battery anode material Mg-Sr-Ge ternary alloy and the commercial AZ31 alloy after discharge prepared in Examples 1 to 2 of the present invention. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0020] In the following examples of the present invention, unless otherwise specified, all raw materials used are common commercial products that can be directly purchased in the art. Room temperature refers to 25±5°C.
[0021] Example 1 A magnesium-air battery anode material Mg-Sr-Ge ternary alloy, the mass percentage composition of the anode material Mg-Sr-Ge ternary alloy is: Sr 0.1 wt.%, Ge 0.1 wt.%, and the balance is Mg; the preparation method thereof comprises the following steps: 1) High-purity magnesium ingots (Mg purity is 99.99%), high-purity germanium (Ge purity is 99.99%) and Mg-20Sr master alloy are used as raw materials, and the raw materials are weighed according to the mass ratio (i.e., mass percentage: Mg 99.8%, Sr 0.1%, Ge 0.1%); after weighing, these raw materials are mechanically polished to remove the surface oxide layer. Subsequently, the raw materials are washed with anhydrous ethanol to ensure that all residual impurities are removed, and finally dried.
[0022] 2) Place the dried high-purity magnesium ingot, high-purity germanium and Mg-20Sr master alloy into the graphite crucible of the vacuum induction melting furnace; first, perform a vacuum operation to remove the air in the furnace. Then, introduce high-purity argon gas with a purity of 99.99%. This step is repeated three times to ensure that the residual air in the furnace is completely exhausted, so that the melting is carried out under the protective atmosphere of argon gas.
[0023] 3) Through program temperature control, the furnace temperature is uniformly raised to 750℃ at a rate of 1℃ / S, and then it is allowed to stand for 5 minutes to ensure that all raw materials are completely melted, and then the molten material is uniformly stirred at a rate of 100 r / min for 20 minutes; to promote the uniform distribution of alloy components. After stirring, it is kept warm and allowed to stand for 5 minutes again, and then the molten alloy is cast into a pre-prepared graphite mold at a temperature of 750℃. After casting, the alloy is cooled to room temperature with the furnace to form a cast Mg-Sr-Ge ternary alloy, which is recorded as Mg-0.1Sr-0.1Ge.
[0024] Example 2 A magnesium-air battery anode material Mg-Sr-Ge ternary alloy, the mass composition percentage of the anode material Mg-Sr-Ge ternary alloy is: Sr 0.1 wt.%, Ge 0.5 wt.%, and the balance is Mg; the preparation method thereof comprises the following steps: 1) High-purity magnesium ingots (Mg purity is 99.99%), high-purity germanium (Ge purity is 99.99%) and Mg-20Sr master alloy are used as raw materials, and the raw materials are weighed according to the mass ratio (i.e., mass percentage: Mg 99.4%, Sr 0.1%, Ge 0.5%); after weighing, these raw materials are mechanically polished to remove the surface oxide layer. Subsequently, the raw materials are washed with anhydrous ethanol to ensure that all residual impurities are removed, and finally dried.
[0025] 2) Place the dried high-purity magnesium ingot, high-purity germanium and Mg-20Sr master alloy into the graphite crucible of the vacuum induction melting furnace; first, perform a vacuum operation to remove the air in the furnace. Then, introduce high-purity argon gas with a purity of 99.99%. This step is repeated three times to ensure that the residual air in the furnace is completely exhausted, so that the melting is carried out under the protective atmosphere of argon gas.
[0026] 3) Through program temperature control, the furnace temperature is uniformly raised to 750℃ at a rate of 1℃ / S, and then it is allowed to stand for 5 minutes to ensure that all raw materials are completely melted, and then the molten material is uniformly stirred at a rate of 100 r / min for 20 minutes; to promote the uniform distribution of alloy components. After stirring, it is kept warm and allowed to stand for 5 minutes again, and then the molten alloy is cast into a pre-prepared graphite mold at a temperature of 750℃. After casting, the alloy is cooled to room temperature with the furnace to form a cast Mg-Sr-Ge ternary alloy, which is recorded as Mg-0.1Sr-0.5Ge.
[0027] Application test Discharge performance test of magnesium-air battery with Mg-Sr-Ge ternary alloy as anode.
[0028] A magnesium-air battery was assembled with Mg-Sr-Ge ternary alloy as anode, 3.5 wt.% NaCl as electrolyte, and air cathode. The battery discharge performance test was carried out in the magnesium-air battery assembly kit using a Blue Power Battery Test System (Model CT3001A). The test covered a range of current densities, namely 1, 2.5, 5, 10, and 20 mA cm -2 The discharge time at each current density was set to 24 hours. To ensure the accuracy of the test, the Mg-Sr-Ge ternary alloy anode was encapsulated in silicone rubber to ensure that only 1.0 cm 2 The Mg-Sr-Ge ternary alloy anode used for battery testing is encapsulated in silicone rubber, and the area exposed to the test solution is 1.0 cm 2 . Before all experiments began, the anode surface was mechanically ground using sandpaper (metallographic sandpaper: 180-600-1500-3000) to remove the surface oxide layer and impurities to ensure that the surface was flat and free of obvious defects. The ground anode surface was cleaned with anhydrous ethanol to remove residual grinding particles and impurities and further clean the surface. The cleaned anode was naturally dried at room temperature to remove surface moisture. After drying, the mass of the anode before discharge was weighed. The air cathode (Changzhou Youteke, M20) consists of a gas diffusion layer, a current collecting layer and a catalytic layer, in which the catalytic layer includes a manganese dioxide catalyst. After the battery discharge test, 200 g L -1 The anode surface was treated with a chromic acid solution to remove the sediment and impurities generated during the discharge process. The treated anode was naturally dried at room temperature, and then weighed to record the mass of the anode after discharge. According to the mass change of the anode before and after discharge, the anode utilization efficiency, specific capacity and specific energy of the magnesium-air battery were calculated using the following formula.
[0029] Among them, W theo (g) is the theoretical weight loss of the anode, W tota l (g) is the actual weight loss obtained by the difference in anode mass before and after discharge; I (A) is the applied current, t (h) is the discharge time; U (V) is the discharge voltage; F is the Faraday constant (26.8 A hmol -1 ), x i 、n i 、m i are the mass fraction, number of exchange electrons and atomic weight of each element in the material respectively.
[0030] Figure 1The average discharge voltage, anode utilization efficiency, specific capacity and specific energy values of Mg-Sr-Ge alloys with different contents and commercial AZ31 alloy are shown in Figure 2. At all current densities, the Mg-0.1Sr-0.1Ge alloy exhibits the best discharge performance. Specifically, at 10 mA cm -2 At a current density of 20 mA cm, the discharge voltage of the alloy is as high as 1.603 V, while the discharge voltage of the commercial AZ31 alloy is only 1.487 V. -2 When the anode utilization efficiency and specific capacity of Mg-0.1Sr-0.1Ge alloy were 63.58% and 1400.55 mAh g -1 , while the corresponding values of AZ31 alloy are 60.1% and 1331.37 mAh g -1 In addition, at 10 mA cm -2 At a current density of 1.34 W / kg, the specific energy value of the Mg-0.1Sr-0.1Ge alloy reached 1960.54 Wh / kg -1 This value significantly exceeds the 1689.01 Wh Kg of commercial AZ31 alloy. -1 These data indicate that the Mg-0.1Sr-0.1Ge alloy has significant discharge performance advantages.
[0031] Figure 2 The anode surface and cross-sectional morphology of Mg-Sr-Ge alloys with different contents and commercial AZ31 alloy after discharge. It can be seen from the figure that the surface of Mg-0.1Sr-0.1Ge is mainly fine cracks, which provides sufficient reactive area for the anode surface. Its surface discharge product layer is also the thinnest, only 12.8 μm, so Mg-0.1Sr-0.1Ge has the highest discharge voltage. Compared with the commercial AZ31 alloy, its surface after discharge is uneven, and the discharge product layer is thicker, reaching 45.7 μm. This thick discharge product layer seriously hinders the further discharge of the AZ31 alloy and affects its electrochemical performance.
[0032] In summary, the Mg-Sr-Ge ternary alloy proposed in the present invention effectively improves the discharge voltage of the magnesium anode and enhances the anode utilization efficiency of the magnesium-air battery by adding Sr (strontium) and Ge (germanium) elements in appropriate amounts. Among various alloy combinations, the Mg-0.1Sr-0.1Ge ternary alloy exhibits the highest anode utilization efficiency and the highest specific energy. Therefore, from the perspective of comprehensive performance, the Mg-0.1Sr-0.1Ge alloy is considered to be an ideal anode material for magnesium-air batteries due to its excellent discharge performance. This provides a new direction for the development of magnesium-air battery technology, and is expected to achieve more efficient and longer-lasting energy storage solutions.
Claims
1. A magnesium-air battery anode material Mg-Sr-Ge ternary alloy, characterized in that: The chemical composition is calculated by mass percentage as follows: strontium 0.1~2.0 wt%, germanium 0.1~2.0 wt%, and the balance is magnesium.
2. The magnesium-air battery anode material Mg-Sr-Ge ternary alloy according to claim 1, characterized in that: The chemical composition is calculated by mass percentage as follows: strontium 0.1wt%, germanium 0.1wt%, and the balance magnesium.
3. The magnesium-air battery anode material Mg-Sr-Ge ternary alloy according to claim 1, characterized in that: The chemical composition is calculated by mass percentage as follows: strontium 0.1wt%, germanium 0.5wt%, and the balance magnesium.
4. The method for preparing the Mg-Sr-Ge ternary alloy as the anode material of the magnesium-air battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Weigh pure magnesium ingot, pure germanium and Mg-Sr master alloy in proportion, and remove the oxide layer on the surface; (2) The above raw materials are placed in a vacuum melting furnace, heated under a protective atmosphere until the raw materials are completely melted, stirred, then kept warm and allowed to stand for 5-20 minutes, and finally cast to obtain a cast ternary alloy.
5. The method for preparing the magnesium-air battery anode material Mg-Sr-Ge ternary alloy as claimed in claim 4, characterized in that: The heating temperature is 720℃-750℃, and the stirring is for 10-30 minutes.
6. The method for preparing the magnesium-air battery anode material Mg-Sr-Ge ternary alloy as claimed in claim 4, characterized in that: The protective atmosphere used is high-purity argon with a purity of not less than 99.99%.
7. The method for preparing the magnesium-air battery anode material Mg-Sr-Ge ternary alloy as claimed in claim 4, characterized in that: The Mg-Sr master alloy used is Mg-20Sr master alloy.
8. Use of the Mg-Sr-Ge ternary alloy according to any one of claims 1 to 3 as an anode material for magnesium-air batteries.
9. A magnesium-air battery, characterized in that: The invention comprises an electrolyte, an air cathode and the anode material Mg-Sr-Ge ternary alloy as claimed in any one of claims 1 to 3.
10. The magnesium-air battery according to claim 9, characterized in that: The electrolyte is a 3-4 wt.% sodium chloride solution.